Pharmacokinetic–pharmacodynamic analysis of cefmetazole against extended-spectrum β-lactamase-producing Enterobacteriaceae in dogs using Monte Carlo Simulation - Kusumoto, Mizuki; Motegi, Tomoki; Uno, Haruna; Yokono, Mizuki; Harada, Kazuki (Frontiers in Veterinary Science, 2023)
Introduction The spread of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-E) is a serious concern in companion animal medicine owing to their ability to develop multidrug resistance. Cefmetazole (CMZ) is a candidate drug for treating ESBL-E infections; however, its regimen in dogs has not been established. In this study, we investigated the pharmacokinetic (PK) indices of CMZ in dogs and performed PK–pharmacodynamic (PD) analyses using Monte Carlo Simulation (MCS). Methods In total, six healthy dogs received an intravenous bolus dose of CMZ (40 mg/kg body weight). Serum CMZ concentrations were evaluated using liquid chromatography–mass spectrometry, and PK indices were determined based on non-compartmental analysis. The PK–PD cut-off (COPD) values were calculated as the highest minimum inhibitory concentration (MIC) that achieved ≥90% probability of target attainment for a target value of unbounded drug concentration exceeding 40% of the dosing interval. The cumulative fraction of response (CFR) was calculated based on the MIC distribution of wild-type ESBL-E from companion animals. Results The area under the concentration–time curve and elimination half-time were 103.36 ± 7.49 mg·h/L and 0.84 ± 0.07 h, respectively. MCS analysis revealed that COPD values for regimens of 40 mg/kg q12, q8h, and q6h were ≤ 0.5, ≤2, and ≤ 4 μg/mL, respectively. A regimen of 40 mg/kg q6h was estimated to achieve a CFR of 80–90% for Escherichia coli and Klebsiella pneumoniae. By contrast, all regimens exhibited a CFR of ≤70% for Proteus mirabilis and Enterobacter cloacae. Discussion We conclude that CMZ at 40 mg/kg q6h could be a viable treatment regimen for dogs infected with ESBL-producing Escherichia coli and Klebsiella pneumoniae.